The safeguard of built heritage in archeological sites, an interdisciplinary approach based on light-weight UAV photogrammetry and terrestrial laser scanning survey - Prati, Davide (DIDApress, Dipartimento di Architettura Università degli Studi di Firenze, 2020)
The use of digital technological tools for the architectonic and the archeological survey is increasingly widespread, and, in recent years, it is gaining importance due to the many exploitable applications, from 3D modeling to the cultural heritage safeguarding. This paper aims to illustrate the potential of the complementary use of terrestrial phase-shift laser scanning with UAV air photogrammetry to set up a workflow in order to produce vulnerability and safety analysis of remains belonging to the archeological sites starting from a 3D geometrical model. The proposed approach has been applied to the medieval tower located on the top of “Monte Lucio” (309 m. above mean sea level), one of the four peaks situated on the southern municipal border of “Quattro Castella”, in the province of “Reggio Emilia” (Italy). This building is part of a small medieval archeological site dating from the end of the 13th century. The 2011 excavations in the area surrounding the tower brought to light the remains of various medieval constructions, including a small religious building, known as Saint Leonard church. In order to perform an in-depth vulnerability analysis of this ancient tower, an interdisciplinary collaboration between different professional figures as archeologists and chemists was established to get all-around information. First of all, an exhaustive stratigraphic analysis was carried out through laboratory tests on the mortar that made it possible to date the different construction phases of the tower. This allowed fine-setting the material characterization parameters then embedded into structural models, usually the most complex operation in masonry archeological buildings. Alongside the analysis, a geometrical survey identified the tower dimensions. A very accurate dimensional data of the basement was obtained with a terrestrial laser scanner; More detailed information on the tower top, inaccessible to laser equipment, was acquired using UAV photogrammetry, a particularly effective technology when the surveyed ...